Peran Komunikasi Mri Surabaya Dalam Pengimplementasian Program Bantuan Pemberdayaan Kampung Kali Jagir - Indah, Ghizarah Faradilla Al; Sinaga, Michaela N. C.; Geraldine, Salsabilla; Agustin, Amadhea Kahanaya Putri; Zuhri, Saifuddin (Komunika : Jurnal Ilmiah Komunikasi, 2024)
Communication as a form of interaction within an organization creates expectations and roles with certain responsibilities. As an institution that is actively committed to community empowerment, MRI Surabaya has an organizational structure that is formed specifically to support the success of the program and the success of the organization. The purpose of this research is to explore the role of organizational communication in supporting MRI Surabaya's community empowerment program towards Kali Jagir Village by applying a qualitative method and descriptive approach conducted through in-depth interviews with 2 key informants (chairman of MRI Surabaya and residents of Kali Jagir Village ), as well as field observations as data collection techniques and facts that actually occur. The two-way communication that is applied creates active involvement of residents in the empowerment program provided and is able to increase the effectiveness of program success.